Corelation of Physical Activity to Blood Sugar Levels in Patients with Diabetes Mellitus in Juhan Asa Village - Nika Nika (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Physical activity in diabetes mellitus plays a role in regulating blood glucose levels. The main problem in diabetes mellitus is the lack of response to insulin (resistance to insulin) so that glucose cannot enter the cells. Objective: To see the correlation between physical activity and blood sugar levels in patients with diabetes mellitus in Juhan Asa village. Methods: obtained p value 0.007 (<0.05) which means H1 is accepted and H0 is rejected, meaning that there is a relationship between physical activity and sugar levels in people with diabetes mellitus in Juhan Asa village. Results and Discussion: Otained p value 0.007 (<0.05) which means H1 is accepted and H0 is rejected, meaning that there is a relationship between physical activity and sugar levels in people with diabetes mellitus in Juhan Asa village. Then obtained an Odd Ratio of 0.636 which means that physical activity has a risk of 0.636 times on blood sugar levels, then the odds ratios of 0.464-0.873 have a close range, which means that physical activity has a weak relationship. Conclusion: There is a relationship between physical activity and sugar levels in people with diabetes mellitus in Juhan Asa village. It is expected that people with Diabetes Mellitus apply good physical activity in order to control their blood sugar levels.